Effect of Pressure-Cooking Time Method on the Characteristics of Abon Entok - Choirul Anwar; Nur Agustin Mardiana; David Kurniawan; Anang Widigdyo; Yanna Naila Zulfa; Aditya Wirawantoro Putra (G-Tech: Jurnal Teknologi Terapan, 2025)
Abon is a dry meat-based product typically made from beef, chicken, or other types of poultry, including entok. In the production of abon, the boiling stage is critical, as it determines the tenderness of the meat, which directly influences the shredding process and the overall quality of the final product. However, conventional boiling methods often require extended cooking times to achieve the desired tenderness. To address this limitation, high-pressure cooking using a pressure cooker has become a common alternative due to its ability to significantly reduce cooking time without compromising product quality. Therefore, the objective of this study was to evaluate the effect of cooking time on the physical, chemical, and sensory characteristics of abon entok. This study employed a single independent variable, namely boiling time, which was applied in three treatment durations (15, 25, and 35 minutes). Based on the results of the analysis of the physical, chemical and sensory parameters of abon entok, it was found that boiling time had no significant effect on the physical parameters (pH and cooking loss) and certain sensory attributes (aroma, taste, and overall acceptability). In contrast, it had a significant effect (p<0.05) on the sensory attributes of color and texture. However, the multiple attribute Zeleny analysis identified the 15-minute boiling time (treatment A) as the best overall treatment, producing pH of 6.20 ± 0.07, cooking loss of 42.99 ± 1.50%, colour score of 3.60, aroma score of 4.07, texture score of 3.37, taste score of 3.77, and overall appearance score of 3.97.